The Doctor's Garden Medicine, Science, and Horticulture in Britain - Hickman, Clare (Yale University Press, 2021)
As Britain grew into an ever-expanding empire during the late eighteenth and early nineteenth centuries, new and exotic botanical specimens began to arrive within the nation's public and private spaces. Gardens became sites not just of leisure, sport, and aesthetic enjoyment, but also of scientific inquiry and knowledge dissemination. Medical practitioners used their botanical training to capitalize on the growing fashion for botanical collecting and agricultural experimentation in institutional, semipublic, and private gardens across Britain. This book highlights the role of these medical practitioners in the changing use of gardens in the late Georgian period, marked by a fluidity among the ideas of farm, laboratory, museum, and garden. Placing these activities within a wider framework of fashionable, scientific, and economic interests of the time, historian Clare Hickman argues that gardens shifted from predominately static places of enjoyment to key gathering places for improvement, knowledge sharing, and scientific exploration.